"The Ethiopian livestock industry: Retrospects and prospects" - Jutzi, S.C. (Institute of Agricultural Research, 1990)
Reviews vertisol management research experiences in Ethiopia. Discusses the relative potential of vertisols and Development of the Ethiopian Vertisol Program. Examines integration of research programmes and technology extension. Presents data on th economic evaluation of improved, animal-powered surface drainage at Inewari and Were Ilu.